2008
DOI: 10.1186/1471-244x-8-22
|View full text |Cite
|
Sign up to set email alerts
|

Five-Factor Model personality profiles of drug users

Abstract: Background: Personality traits are considered risk factors for drug use, and, in turn, the psychoactive substances impact individuals' traits. Furthermore, there is increasing interest in developing treatment approaches that match an individual's personality profile. To advance our knowledge of the role of individual differences in drug use, the present study compares the personality profile of tobacco, marijuana, cocaine, and heroin users and non-users using the wide spectrum Five-Factor Model (FFM) of person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

38
310
4
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(360 citation statements)
references
References 58 publications
38
310
4
8
Order By: Relevance
“…Still, in keeping with previous studies [25], we found that for most variables introduced, cigarette smokers have not been not as severely impaired as the SUD patients. In particular, although cigarette smokers have been similar to the SUD patients with respect to their anxiety and depression levels at assessment, their overall inclination to display these traits was much lower.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Still, in keeping with previous studies [25], we found that for most variables introduced, cigarette smokers have not been not as severely impaired as the SUD patients. In particular, although cigarette smokers have been similar to the SUD patients with respect to their anxiety and depression levels at assessment, their overall inclination to display these traits was much lower.…”
Section: Discussionsupporting
confidence: 75%
“…This suggests that the underlying cognitive-motivational dispositions orienting towards chronic smoking have a lot in common with those relevant to addiction in general. Indeed, other studies have also demonstrated that tobacco users fare in-between heroin users and normal controls in adaptive and maladaptive personality attributes [25].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicates that increased novelty seeking, which is part of openness to experience, is linked to Internet addiction in college students (Ko et al, 2010). Similarly, openness to experience has been found to be associated with marijuana use (Terracciano, Löckenhoff, Crum, Bienvenu, & Costa, 2008). From this, it appears that characteristics indicative of resourcefulness and openness to experience, such as creativity, imagination, and innovation may lead adolescents to engage in pleasurable activities, such as using the Internet, excessively.…”
Section: Discussionmentioning
confidence: 92%
“…Independent of the clusters, high neuroticism and low agreeableness were consistent dimensional characteristics of personality disorders in young adults (Moran et al, 2006). Substance use disorders, especially smoking (Terracciano and Costa, 2004), alcohol (Malouff et al, 2007), marijuana (Terracciano et al, 2008), and polysubstance abuse (McCormick et al, 1998) have also been associated with a high neuroticism/low agreeableness phenotype. The CNR1 gene has been associated with substance use disorders (Zhang et al, 2004;Zuo et al, 2007) and this association might be driven by the common personality structure influenced by this gene, as we have demonstrated in this study.…”
Section: Discussionmentioning
confidence: 99%